2020
DOI: 10.1155/2020/7381391
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional-Printed Poly-L-Lactic Acid Scaffolds with Different Pore Sizes Influence Periosteal Distraction Osteogenesis of a Rabbit Skull

Abstract: The repair of bone defects is a big challenge in reconstructive surgery. Periosteal distraction osteogenesis (PDO), as a promising technique used for bone regeneration, forms a space between the periosteum and bone cortex to regenerate the new bone merely by distracting the periosteum. In order to investigate the influence of distractor framework on the PDO, we utilized three-dimensional (3D) printing technology to fabricate three kinds of poly-L-lactic acid (PLLA) scaffolds with different pore sizes in this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Based on titles and abstracts, 31 studies were selected. Finally, after reading full text and applying study criteria, 24 studies [2,[4][5][6][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] were included in the review (inter-reviewer agreement k = 0.96). The 24 studies selected involved 481 patients with 482 devices.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on titles and abstracts, 31 studies were selected. Finally, after reading full text and applying study criteria, 24 studies [2,[4][5][6][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] were included in the review (inter-reviewer agreement k = 0.96). The 24 studies selected involved 481 patients with 482 devices.…”
Section: Resultsmentioning
confidence: 99%
“…The periosteal distraction technique can be used for the reconstruction of bony defects in the forehead region in the craniomaxillofacial surgery or in neurosurgery; solve problems of bone deficit in the alveolar bone in oral implantology; or for volume deficits that sometimes occur in vertical distraction or bone grafts [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…One example combined PLA with gelatin and added bFGF to form scaffolds that promoted angiogenesis and hepatocyte survival and function after implantation into the mesentery of hepatectomized rats [ 105 ]. It is reported that injection of PLA and PLLA causes stimulation of macrophage-mediated inflammation leading to erythema, swelling and bruising, which should be a consideration in future transplantation applications [ 197 ].…”
Section: Biomaterials For Cell Transplantation To the Livermentioning
confidence: 99%
“…Synthetic polymers are also found in different groups: Biodegradable biomaterials including poly(lactic acid) (PLA), poly(glycolic acid) (PGA), poly(vinyl alcohol) (PVA) and their copolymers. They are commonly used in regenerative medicine for differentiation assays of stem cells progenitors [ 73 , 74 ]. Non-biodegradable biomaterials such as poly(ethylene glycol) (PEG) [ 75 ], 2-hydroxyethyl methacrylate (HEMA) and acrylamide (AAm) [ 76 ].…”
Section: Three-dimensional Culture Systemsmentioning
confidence: 99%
“…Biodegradable biomaterials including poly(lactic acid) (PLA), poly(glycolic acid) (PGA), poly(vinyl alcohol) (PVA) and their copolymers. They are commonly used in regenerative medicine for differentiation assays of stem cells progenitors [ 73 , 74 ].…”
Section: Three-dimensional Culture Systemsmentioning
confidence: 99%